Multi-responsive nanocomposite membranes of cellulose nanocrystals and poly(N-isopropyl acrylamide) with tunable chiral nematic structures. (15th March 2020) - Sui, Yanqiu; Li, Xiaofeng; Chang, Wei; Wan, Hao; Li, Wei; Yang, Fan; Yu, Zhong-Zhen
Graphical abstract: Highlights: Photonic membrane is fabricated by co-assembly of PNIPAM grafted CNC and WPU. The membrane shows varied iridescent colours with varying the PNIPAM contents. The membrane exhibits excellent responses to humidity with cyclic stability. The membrane presents reversible responses to temperatures and solvents. Abstract: By imitating the unique structure of nature creatures, photonic membranes with periodic chiral helical structure can be assembled by cellulose nanocrystals (CNCs). It is still an issue to fabricate CNC photonic structures tunable in the entire visible spectrum with multiple stimuli-response capacities. Herein, a multi-responsive nanocomposite photonic membrane is fabricated by co-assembly of poly(N-isopropyl acrylamide) (PNIPAM) grafted CNCs with waterborne polyurethane (WPU) latex on the basis of the chiral nematic structure of CNCs, the thermo-responsibility of PNIPAM, and the flexibility of WPU. The flexible photonic membranes with uniform structural colors from blue to red are obtained by tuning the PNIPAM content. The membrane exhibits reversible responses to solvents, and iridescence changes in response to relative humidity with excellent repeatability. Interestingly, the membrane can be transparent or opaque depending on the ambient temperature. The photonic membranes are appealing in applications as humidity sensor, camouflage materials, and even smart windows.